Genetic polymorphisms of human platelet antigens in Euro-African and Japanese descendants from Parana, Southern Brazil. (18th August 2017) - Silvestre, Ana Paula Avenia; Zacarias, Joana Maira Valentini; Guelsin, Gláucia Andréia Soares; Visentainer, Jeane Eliete Laguila; Sell, Ana Maria
Abstract: The frequency distributions of HPA-1 to HPA-6 and HPA-15 were evaluated in two Brazilian populations from Parana: a mixed population of predominantly Caucasians and a population of Japanese descendants. Genotyping was performed by PCR-SSP in 364 unrelated individuals. Differences in the distribution of HPA highlight diversity in Brazilian miscegenation and the importance of formation of the HPA panel composed of regional blood donors.